Highly Stereoselective [4+2] and [3+2] Spiroannulations of 2‐(2‐Oxoindolin‐3‐ylidene)acetic Esters Catalyzed by Bifunctional Thioureas. Issue 31 (1st June 2015) - Monari, Magda; Montroni, Elisa; Nitti, Andrea; Lombardo, Marco; Trombini, Claudio; Quintavalla, Arianna
Abstract A new Michael–Michael cascade reaction between 2‐(2‐oxoindolin‐3‐ylidene)acetic esters 1 and nitroenoates 2, catalyzed by bifunctional thioureas, is investigated. The combination of the two Michael reactions results in a novel and facile [4+2] or [3+2] spiroannulation process, which is characterized by the following features: 1) two carbon–carbon bonds and four stereocenters, including a quaternary spiro carbon, are formed under mild conditions; 2) an unprecedented and stereochemically defined substitution pattern on the spirocarbocyclic unit is obtained; 3) the double‐bond configuration of the donor–acceptor nitroenoate 2 determines the absolute configuration of the spiro center, whereas the remaining stereocenters are formed under control of the catalyst. The effect on the final stereochemical outcome of structural variations of each starting material, catalyst, and experimental conditions is analyzed in detail. In particular, the use of specifically designed chiral nitroenoates enables diverse polyfunctional spirocyclohexane derivatives containing six consecutive stereogenic centers to be constructed. To our knowledge, this is the first asymmetric organocatalytic strategy enabling both five‐ and six‐membered β‐nitro spirocarbocyclic oxindoles.